“Evaluación de enfermedades fungosas y prueba de fungicidas para hongos fitopatógenos en semilla de arroz en el bajo mayo” - Córdova Flores, Michel (2006)
The present work of investigation tube like objective to isolate and to identify the mushrooms fitopatógenos that are inside the seeds of rice stops then to carry out the test of fungicidas and to determine which makes a better control to the patogenos of the fungicidas, this one carries out in the atmospheres of the laboratory of vegetable sanity of the National University of San Martín, it is located in Morales's district, County of San Martin, the design that you employment far the execution of the investigation work was the Design Totally at random (first DCA),lo that he/she was carried out it was the gathering of the samples of different producers which were taken to the laboratory to carry out the isolation in humid camera, later on already with the patogenos in growth inside the badges was carried out the chiming to the badges petri that contained the means of appropriate cultivation for the growth and the obtaining of the pure patogenos, in this case it was Pope Dextrosa Agar (PDA), later on he/she was carried out the identification of the patogenos with the she helps of the microscope and the keys taxonomicas of Barneth (1973), Ellis (1971 - 1976), the parameters that were evaluated were the symptoms, the characteristic biometricas and morphology of the patogeno, and after that whole process you arrives to the test of the fungicides with the identified mushrooms that were Diplodia sp; Aspergillus niger; Fusarium sp; Helminthosporium oryzae and Rhizoctonia sp., where the fungicidas that better they controlled to the mushrooms opposing fitopatógenos they were They Captan and Homai, the mushrooms Diplodia sp and Aspergil/us niger showed something from resistance to the fungicides used in the investigation work, and the fungicida! Antracol that showed a light control to the patogenos.